2001
DOI: 10.1007/s002200100484
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Dimensional BF Theories¶in the Batalin-Vilkovisky Formalism:¶The BV Action and Generalized Wilson Loops

Abstract: ABSTRACT. This paper analyzes in details the Batalin-Vilkovisky quantization procedure for BF theories on an n-dimensional manifold and describes a suitable superformalism to deal with the master equation and the search of observables. In particular, generalized Wilson loops for BF -theories with additional polynomial B-interactions are discussed in any dimensions. The paper also contains the explicit proofs to the Theorems stated in [16].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…For a definition of generalized holonomy see Section 6 (and Cattaneo and Rossi [4]). For a loop 2 LM , representing an element of H…”
Section: ‰W H Smentioning
confidence: 99%
See 2 more Smart Citations
“…For a definition of generalized holonomy see Section 6 (and Cattaneo and Rossi [4]). For a loop 2 LM , representing an element of H…”
Section: ‰W H Smentioning
confidence: 99%
“…We will later, in equations (3)(4)(5) and (3)(4)(5)(6), apply the above to fibers of appropriate bundles.…”
Section: Invariant Functions and Principal Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Those may be viewed as the A ∞ -category structure on D b (Coh(X), whose compositions are given by correlation functions. 18 . Being an A ∞ -category (as the collection of all A ∞ modules over the A ∞ -algebra (O(ΠT X), ∂)) it satisfies a certain MC equation.…”
Section: Towards Physical Descriptions Ofmentioning
confidence: 99%
“…More fundamentally we showed that topological open membrane theory can describes and control A, B and C models of topological closed string as different boundary theories. The relation between A and B models are much like different twistings of the same superconformal 18 It is rather correlation maps than correlation functions, though we will stick to the original terminology field theory. Furthermore the topological open membrane theory leads to further (bulk) deformations of the mathematical or physical structure of the boundary string theory.…”
Section: Topological Open P-branes and Generalized Homological Mirrormentioning
confidence: 99%